Applying the China’s marine resource-environment carrying capacity and spatial development suitability approach to the Bay of Biscay (North-East Atlantic) - Borja, Angel; Pouso, Sarai; Galparsoro, Ibon; Manca, Eleonora; Vasquez, Mickaël; Lu, Wenhai; Yang, Lu; Uriarte, Ainhize (Frontiers in Marine Science, 2022)
The EMOD-PACE project, funded by the European Commission, aimed to promote international ocean governance between EU and China. One of the objectives of EMOD-PACE is to compare European and Chinese modelling approaches for ecosystem vulnerability assessment. In particular, our objective was to test the applicability of the Chinese evaluation approach of resource-environment carrying capacity (MRECC) and spatial development suitability (abbreviated as “double evaluation”) to a European sea (the Bay of Biscay), in the context of marine spatial planning. The methodology involves three different steps: (i) an evaluation of areas of ecological importance, which includes species and habitats (i.e., biodiversity protection) and coastal characteristics; (ii) assessment of current marine development and utilization; and (iii) an ecological risk identification and the evaluation of the MRECC, by intersecting results from (i) and (ii). After collating information for 31 species of interest (fish, reptiles, mammals and birds), seven habitats (seagrass, seaweeds, saltmarshes, fish spawning areas, tidal flats, estuaries and unique habitats), marine protected areas and eight current human activities performed at sea (aquaculture, ports, ocean energy facilities, shipping, aggregate extraction and dredging, fisheries, military areas and tourism and recreation), they were aggregated and intersected (ecological data vs. human activities), and the ecological risk was determined. Since the total area covered by Marine Protected Areas and areas of high ecological importance is 135,372 km2, the available carrying capacity for development of marine activities within the Bay of Biscay is 229,266 km2. When we apply weighting to the calculation of the ecological importance and human activities, the high importance areas increase and the available carrying capacity decreases by 0.2%, to 228,637 km2. In this work we demonstrate that the Chinese double evaluation approach can be adapted and applied to a European sea, but to obtain more accurate results, and more extensive application to different areas are needed. Also, we have identified essential improvements, including better information for a number of species and habitats; more robust methods to identify biodiversity priorities; additional fish life-story traits; include future human activities; risks posed by multiple activities; and use appropriate weights through a stakeholder consultation.